Kunst und Video; Internationale Entwicklung und Künstler. - Gruber, B.; Vedder, M. (Köln : DuMont Buchverlag, 1983)
Acconci, Vito ; Ant Farm ; Antin, Eleanor ; Baldessari, John ; Bengils, Lynda ; Burden, Chris ; Cameron, Eric ; Campus, Peter ; Davis, Douglas ; Dibbets, Jan ; de Domenicis, Gino ; Downey, Juan ; Emschwiller, Ed ; Export, Valie ; Fox, Terry ; Freed, Hermine ; Froese, Dieter ; Gerz, Jochen ; Gilbert & George ; Gillette, Frank ; Graham, Dan ; Gusella, Ernest ; Hall, David ; Hocking, Ralph ; Holt, Nancy ; Hoover, Nan ; Horn, Rebecca ; Iimura, Taka ; Jonas, Joan ; Kahlen, Wolf ; Knoebel, Imi ; Korot, Beryl ; Kos, Paul ; Kriesche, Richard ; Kubota, Shigeko ; Landry, Richard ; Levine, Les ; Mann, Andy ; Muntadas, Antoni ; Nauman, Bruce ; Oppenheim, Dennis ; Otth, Jean ; Paik, Nam June ; Palestine, Charlemagne ; Pezold, Friederike ; Rosenbach, Ulrike ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Schneider, Ira ; Serra, Richard ; Sonnier, Keith ; Tambellini, Aldo ; Telethon ; Vasulka, Steina & Woody ; Viola, Bill ; Vostell, Wolf ; Walker, Willie ; Wegman, William ; Weibel, Peter ; Weiner, Lawrence ; Yalkud, Jud
boek